2000
DOI: 10.1007/pl00000010
|View full text |Cite
|
Sign up to set email alerts
|

Presenting Dynamic Information on Mobile Computers

Abstract: A problem with mobile computing devices is the output of dynamic information because their screens are small. This paper describes an experiment to investigate the use of non-speech sounds to present dynamic information without using visual display space. Results showed that nonspeech sound could be used in a simple share-dealing scenario to present a 'sound graph' of share prices. This allowed participants to reduce the workload they had to invest in share-price monitoring as they could listen to the graph wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 5 publications
(4 reference statements)
0
10
0
Order By: Relevance
“…Brewster and Murray [10] investigated the application of sound to enhance the usability of mobile personal digital assistant (PDA) devices. Participants were required to maximize profit by trading shares using either a simple auditory display or a line graph to monitor price changes.…”
Section: Decreasing Subjective Workloadmentioning
confidence: 99%
“…Brewster and Murray [10] investigated the application of sound to enhance the usability of mobile personal digital assistant (PDA) devices. Participants were required to maximize profit by trading shares using either a simple auditory display or a line graph to monitor price changes.…”
Section: Decreasing Subjective Workloadmentioning
confidence: 99%
“…In one experiment, for example, Brewster and Murray mapped stock market price data for a single share to pitch to investigate if sounds provide a viable alternative for trading shares on mobile computing devices with limited screen space. 10 Test subjects' performance was evaluated in a task where the aim was to maximize profit by buying and selling shares. Subjects could use either the sonification or a line graph to monitor the share price over time.…”
Section: Auditory Displaysmentioning
confidence: 99%
“…In the context of mobile applications, Brewster and Murray [3] used Earcons -short sounds associated to UI elements: ear icons-to improve the presentation of dynamic information on mobile devices. A comparison with the traditional visual-only modality in a stock price's monitoring task showed that the use of sonification reduced subjects' workload and their need to switch between several displays.…”
Section: Chi 2010: Sensingmentioning
confidence: 99%